Disciplinary status and scope of the research activity of administration professors - Alvear Vásquez, Janina Daniela; Salán Barrionuevo, Catherine Lizbeth; Castro Analuiza, Juan Carlos (mktDESCUBRE; Vol 1 No 12 (2018): Twelfth Edition - (July - December), 2018)
The excessive concentration or focalization of the research activity, answer to a small number of authors and co-authors, respect to the professors that expect to generate research results. With this disruptive, the research papers of and prospective analysis of professors are analyzed, through a systematic revision where the dynamic and the reach of publications in 2011-2018 of the school of Ciencias Administraticas de la Universidad Tecnica de Ambato are visualized, the center of Educacion Superior located at Zona Tres from in center of Ecuador. The study of an original investigation, exploratory character, where the dynamic and the reach of the research activity are visualized, landed in scientific publications, regional, books, and papers. This process allows the production of 121 publications in 36 journals at local and international level. Most of it is hosted in the Regional system of Online Information to Scientific Journals of Latin America, Caribbean, Spain, and Portugal (Latindex). Finally, the tendency of publications is growing, according to the profile, tone, and young teachers typology that publishes in greater quantity in relation to the two remaining identified segments.